O papel dos receptores 5-HT1A e 5-HT2C da substância cinzenta periaquedutal sobre os efeitos da fluoxetina na antinocicepção induzida pelo confinamento de camundongos aos braços do labirinto em cruz elevado - Baptista de Souza, Daniela (Universidade Federal de São Carlos, 2015)
The pain is an universal experience, and frequently follows anxiety and depression cases. Some specific drugs used in depression and anxiety treatment are also used for the relief of pain. There are evidences showing that exposure to threatening situations can result in pain inhibition. In this way, studies involving pain and anxiety use animal models as tools for potential therapeutic agents screening as well as for enhance the knowledge about the neurobiology of emotions. This study investigated the following effects: acute and chronic fluoxetine treatment; microinjections of 5-HT1A and 5HT2C receptors agonists intraperiaqueductal gray matter (PAG), and the administration combined of these drugs on antinociception induced by the open arms (OAA) of the elevated plus maze (EPM). Furthermore, we investigated the effects of fluoxetine chronic treatment on serotonin, 5- HIAA, 5-HT1A and 5HT2C receptors levels within PAG. Our results showed that: (I) fluoxetine acute treatment (20 mg/kg) was able to increase the OAA; (II) fluoxetine chronic treatment (21 days) (20 mg/kg) also enhances the OAA, and decreased the number of writhes on animal confined in the enclosed arm, featuring an analgesic effect; (III) the administration of 8-OH-DPAT (5-HT1A agonist) intra-PAG did not change the number of writhes in animals confined in the arms of the EPM; (IV) the infusions of mCPP and MK- 212 (5HT2C agonists) intra-PAG increased the OAA. (V) The blockade of 5HT2C receptors located in the PAG by SB 242080 injection (5HT2C antagonist) was able to completely reverse the OAA; (VI) the combined administration of fluoxetine (acute treatment) and 8- OH-DPAT intra-PAG also blocked completely the OAA; (VII) the combined administration of fluoxetine (acute treatment) and MK-212 intra-PAG reversed the increase of OAA observed with MK-212 injection; (VII) combined administration of fluoxetine (chronic treatment) and 8-OH-DPAT intra-SCP once more blocked OAA; (IX) the fluoxetine (chronic treatment) + MK-212 intra-PAG, impairs the OAA increase observed with isolated MK-212 injection; (X) fluoxetine chronic treatment was not capable to change the serotonin, 13 5-HIAA levels, and serotonin turnover in the PAG (XI) fluoxetine chronic treatment promoted up-regulation of 5-HT1A and 5HT2C receptors within PAG. These findings suggest that OAA is médiated by 5-HT2C receptors located in the PAG. Furthermore, fluoxetine was capable to interact with this serotonergic receptor promoting functional (acute treatment) and quantitative (chronic treatment) changes on 5-HT1A and 5HT2C receptors within PAG.
Keywords: Farmacologia; Fluoxetina; Camundongos; Serotonina; Antinocicepção; Labirinto em cruz elevado; Receptores 5-HT1A e 5HT2C; Substância cinzenta periaquedutal; Teste de contorções; Antinociception; Elevated plus-maze; Serotonin; Fluoxetine; 5- HT1A and 5HT2C receptors; Periaqueductal gray matter; Writthing test; Mice; CIENCIAS BIOLOGICAS::FISIOLOGIA